Potato resistance to quarantine diseases - A. V. Khiutti; O. Yu. Antonova; N. V. Mironenko; T. A. Gavrilenko; O. S. Afanasenko (Вавиловский журнал генетики и селекции)
The casual agent of potato wart Synchytrium endobioticum (Schilb.) Perc. and potato golden nematode (PGN) Globodera rostochiensis (Wollenweber) Behrens are the quarantine species causing the most widespread and destructive diseases of potato in the Russian Federation and other countries of the world. The potato pale nematode Globodera pallida (Stone) Behrens is not found in Russia, although in the European Union it is found everywhere. The review provides information on the harmfulness of S. endobioticum and PGN. To date, 43 pathotypes of S. endobioticum and 5 pathotypes of PGN have been revealed in the world. In the Russian Federation, only the first (D1) pathotype of potato wart and pathotype Ro1 of PGN have been found. Modern sets of differentials for S. endobioticum and PGN and methods of pathotype composition determination, including efforts to develop molecular markers (SSR) to determine the race of S. endobioticum, are presented. Data on the resistance of commercial potato cultivars to these quarantine diseases and methods for resistance determination are reviewed. Modern data on the genetics of potato resistance to S. endobioticum, G. rostochiensis and G. pallida, including mapping and cloning of R-genes, are presented. Available literature data on molecular markers of R-genes for marker assisted selection and the evaluation of their effectiveness are presented. The use of multiplex systems allows the presence of several genes for resistance to one or more pathogens to be analyzed at once. Mechanisms of potato quantitative resistance to S. endobioticum and PGN and adaptation processes in pathogens populations resulting in overcoming resistance of host are discussed. Cultivation of cultivars poorly susceptible to PGN can stimulate the adaptive variability of the pathogen and induce virulent pathotypes for 2–3 pathogen generations.